Towards an effective control programme of soil-transmitted helminth infections among Orang Asli in rural Malaysia. Part 2: knowledge, attitude, and practices - Nasr, N.A.; Al-Mekhlafi, H.M.; Ahmed, A.; Roslan, M.A.; Bulgiba, Awang (BMC, 2013)
Background In the first part of this study, we investigated the prevalence and associated key factors of soil-transmitted helminth (STH) infections among Orang Asli children in rural Malaysia; an alarming high prevalence and five key factors significantly associated with infections were reported. Part 2 of this study aims to evaluate the knowledge, attitude and practices (KAP) on STH infections among Orang Asli in Peninsular Malaysia.